Effects of a natural nutritional supplement on immune cell infiltration and immune gene expression in exercise-induced injury - Jiang, Feng; Yang, Rongfeng; Xue, Diya; Li, Rong; Tan, Meiling; Zeng, Zhicong; Xu, Luhua; Liu, Linling; Song, Yinzhi; Lin, Fengxia (Frontiers in Nutrition, 2022)
Inflammatory immune response plays a key role in exercise-induced injury and healing; however, the relevant regulatory mechanisms of immune infiltration in exercise-induced injuries remain less studied. In the present study, a highly efficient system for screening immunity-related biomarkers and immunomodulatory ability of natural nutritional supplements was developed by integrating intelligent data acquisition, data mining, network pharmacology, and computer-assisted target fishing. The findings demonstrated that resting natural killer cells showed a higher rate of infiltration after exercise, whereas naive B cells and activated dendritic cells showed higher rate of infiltration before exercise. Four key genes, namely PRF1, GZMB, CCL4, and FASLG, were associated with exercise-induced injuries and inflammatory immune response. In total, 26 natural compounds such as echinacoside, Eugenol, tocopherol, and casuariin were predicted by using the HERB databases. Molecular docking analysis showed that GZMB, FASLG, and CCL4 bound to echinacoside. In vivo experiments in mice showed that after 30 min swimming, NK cells showed high infiltration rates, and the key genes (GZMB, PRF1, FASLG, and CCL4) were highly expressed; however, echinocandin significantly reduced the level of NK cells and decreased the expression of the four key genes post exercise. This natural nutritional supplement may act to protect against inflammatory injury after exercise by suppressing specific immune infiltration.